Pre-Service English Teacher Identity Development through Reflective Practices: Insights from Kampus Mengajar Program - Maulidia Rachmawati Nur; Nikh Latifah; Erik Yudha Pratama; Eva Nurmayasari (JOLLT Journal of Languages and Language Teaching, 2026)
This qualitative case study explores reflective practice activities experienced by Indonesian pre-service teachers in teaching English for Young Learners during Kampus Mengajar Program initiated by the Goverment of Indonesia. Using Gibbs’ Reflective cycles framework, which includes description, feelings, evaluation, analysis, conclusion, and action plan, this study examines how reflective practice activities during the teaching practicum influence their teacher identity development. Five pre-service teachers were invited to join in this research. Data were collected through close-ended questionnaires and semi-structured interview, then analyzed with Miles and Huberman’s model. The findings indicate that reflective practice activities help them to develop their identity as a teacher, and Kampus Mengajar Program gives them opportunities to improve their teaching skills. The analysis of the data yielded seven categories: Opportunities to reflect, Expression of feelings, Teaching awareness, Lifelong learning, Self-confidence, Self-assessment, and Self-belief. This study highlight the importance of reflective practice activities in shaping the teacher identity and sustain the teacher professional development. The findings suggest that the policy in teacher education is essential to foster reflective practice activites during the teaching practicum.